The Crisis of Causality Voetius and Descartes on God, Nature and Change - van Ruler, Han (Brill, 1995)
The Crisis of Causality deals with the reaction of the Dutch Calvinist theologian Gisbertus Voetius (1589-1676) to the New Philosophy of René Descartes (1596-1650). Voetius not only criticised the Cartesian idea of a mechanical Universe; he also foresaw that shifting conceptions of natural causality would make it impossible for theologians to explain the relationship between God and Creation in philosophical terms. This threatened the status of theology as a scientific discipline. Apart from a detailed analysis of the Scholastic and Cartesian notions of causality, the book offers new perspectives on related subjects, such as seventeenth-century university training and the Cartesian method of science. It will be of great importance to any student of seventeenth-century intellectual history, philosophy, theology and history of science.